Collaborative Governance in Strengthening And Developing Umkm In The City Of Surakarta - Putri Utami, Novi Carlina; Suranto, Joko; Suhita, Damayanti (Universitas Widya Mataram, 2024)
Strengthening and developing MSMEs is a priority for the Surakarta City Industrial SME Cooperative Service. The growth of MSMEs in the City of Surakarta has been positive in the last three years. In 2022, there will be 11,157 micro, small and medium enterprises (MSMEs) in the area. Data from the previous year, 2021, only saw 3,635 MSMEs. Collaboration is essential to create competitive MSMEs. This research aims to explain the strategy of the Industrial SME Cooperative Service in collaborating to advance MSMEs. Collaborative Governance Research Results, De Seve (2007:50) are as follows: Network Structure, the type of collaboration structure applied is Self Governance. Commitment to a common purpose has a different goal than in theory. Trust among the participants, that is, there is trust between stakeholders seen from the running of the collaborative program. Governance, Boundaries, and exclusivity have been fulfilled. Rules have yet to be fulfilled, while self-determination and network management have yet to be implemented firmly. Access to authority, there is a legal basis for implementing the MSME Strengthening and Development program. Distributive Accountability, there are procedures for implementing activities in the form of SOPs made by the Industrial SME Cooperative Service. Information Sharing is shared on MSME activities through the MSME Association WA Group, the Department's Instagram account, and the Industrial SME Cooperative Service website so that MSMEs can easily access it. Access to Resources, three resources have been met, namely human resources, budget and infrastructure. Keywords: Collaborative Governance; Development and Strengthening of MSMEs; Role of the Industrial SME Cooperative Service